The Role of Forkhead Box Family in Bone Metabolism and Diseases - Xu, Jianxiang; Wang, Kanbin; Zhang, Zengjie; Xue, Deting; Li, Weixu; Pan, Zhijun (Frontiers in Pharmacology, 2022)
Forkhead box (Fox) family, an evolutionarily conserved family of transcription factors carrying the ‘Forkhead’ motif, is serving an indispensable role in human health and disease. Fox family are active in cell differentiation, proliferation and apoptosis, embryonic development, aging, glucose and lipid metabolism, and immune regulation. More recently, studies on Fox family in the regulation of bone metabolism and orthopedic diseases have increased, however, a recent comprehensive update on this issue is still lacking. This review highlights the major molecular mechanisms and regulatory actions underlying of Fox factors in bone metabolism, bone development, bone homeostasis and bone diseases associated with Fox factor inhibition /upregulation, as well as drugs targeting actions of Fox-factors-based therapeutics.